1999
DOI: 10.3354/cr011109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial aggregation on predictions of forest climate change response

Abstract: We investigated the influence of spatial aggregation on modeled forest responses to climate change by applying the process-based Terrestrial Ecosystem Model (TEM) to a fine resolution spatial grid (100 km 2 ) and to a coarse resolution spatial grid (2500 km 2 ). Three climate scenarios were simulated: baseline (present) climate with ambient CO 2 and 2 future climates derived from the general circulation models OSU and GFDL-Q with elevated atmospheric CO 2 . For baseline climate, the aggregation error of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The findings of the overall aggregation effect on NPP agrees with the findings of Nungesser et al (1999), who found a mean uncertainty of <2% on NPP by modifying precipitation and solar radiation for resolutions of 10 and 50 km. The average differences for the wheat NN approach in this study (1.2%) is also in this range, but includes a large increase for AgroC of up to 3.3%.…”
Section: Model Specific Aggregation Effectsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the overall aggregation effect on NPP agrees with the findings of Nungesser et al (1999), who found a mean uncertainty of <2% on NPP by modifying precipitation and solar radiation for resolutions of 10 and 50 km. The average differences for the wheat NN approach in this study (1.2%) is also in this range, but includes a large increase for AgroC of up to 3.3%.…”
Section: Model Specific Aggregation Effectsupporting
confidence: 91%
“…In both studies, the impact was minor for averages over the entire study area, but showed impacts for smaller areas, especially for areas dominated by strong relief changes (Pierce and Running, 1995). In both studies, the effects were tested by one model and for two resolutions of 10 and 50 km grid cells in Nungesser et al (1999), and 1 km and 110 km in Pierce and Running (1995). The latter study investigated the effect for different input variables (relief, climate and soil) and found that climate data aggregation was the dominant variable affecting scale differences of NPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relevance of scale (Hansen & Jones 2000, Ewert et al 2011, Nendel et al 2013 and spatial data aggregation (Gardner et al 1982, Cale et al 1983, Cale & O'Neill 1988, Rastetter et al 1992, Pierce & Running 1995, Nungesser et al 1999, Gong et al 2003, Syphard & Franklin 2004, Lorite et al 2005, Ershadi et al 2013 is well known and data aggre gation has been addressed, for instance, in soil or hydrological process modelling (Heuvelink & Pebesma 1999, Haverkamp et al 2005, Leopold et al 2006, Bormann et al 2009, few studies have characterized the effect in application of crop models with spatially aggregated climate input data on simulated regional yields, hereafter called the aggregation effect. For example, De Wit et al (2005) used precipitation and radiation aggregated from 10 to 50 km resolution as model input to simulate winter wheat and grain maize yields in Germany and France.…”
Section: Variability Of Effects Of Spatial Climate Data Aggregation Omentioning
confidence: 99%
“…Differences in the representation of ecosystem processes by ecosystem models may be caused by the following: (1) different conceptualizations of the relationships among ecosystem processes, different formulations of the same ecosystem processes, and different parameterizations of the same formulations Cramer et al 1999;Jenkins et al 1999); (2) the use of different input data sets (Pan et al 1996); (3) application of the models at different spatial resolutions (Jenkins et al 1999;Nungesser et al 1999); or (4) the use of different simulation protocols in applying the models. To identify process-based uncertainties related to differences in conceptualization, formulation, and parameterization among models, it is necessary to minimize differences associated with other sources by standardizing input data sets and simulation protocols, which is a standard practice in formal comparisons among models VEMAP Members 1995;Heimann et al 1998;Cramer et al 1999;Jenkins et al 1999;Kicklighter et al 1999;Schimel et al 2000).…”
Section: Introductionmentioning
confidence: 99%